The ENCODEdb portal: Simplified access to ENCODE Consortium data - Elnitski, Laura L.; Shah, Prachi; Moreland, R. Travis; Umayam, Lowell; Wolfsberg, Tyra G.; Baxevanis, Andreas D. (Genome Research, 2007)
The Encyclopedia of DNA Elements (ENCODE) project aims to identify and characterize all functional elements in a representative chromosomal sample comprising 1% of the human genome. Data generated by members of The ENCODE Project Consortium are housed in a number of public databases, such as the UCSC Genome Browser, NCBI’s Gene Expression Omnibus (GEO), and EBI’s ArrayExpress. As such, it is often difficult for biologists to gather all of the ENCODE data from a particular genomic region of interest and integrate them with relevant information found in other public databases. The ENCODEdb portal was developed to address this problem. ENCODEdb provides a unified, single point-of-access to data generated by the ENCODE Consortium, as well as to data from other source databases that lie within ENCODE regions; this provides the user a complete view of all known data in a particular region of interest. ENCODEdb Genomic Context searches allow for the retrieval of information on functional elements annotated within ENCODE regions, including mRNA, EST, and STS sequences; single nucleotide polymorphisms, and UniGene clusters. Information is also retrieved from GEO, OMIM, and major genome sequence browsers. ENCODEdb Consortium Data searches allow users to perform compound queries on array-based ENCODE data available both from GEO and from the UCSC Genome Browser. Results are retrieved from a specific genomic area of interest and can be further manipulated in a variety of contexts, including the UCSC Genome Browser and the Galaxy large-scale genome analysis platform. The ENCODEdb portal is freely accessible at http://research.nhgri.nih.gov/ENCODEdb.